Soldiers' employment attitude and employability: An exploratory study - Peng Gao; Lunqu Yuan (Journal of Industrial Engineering and Management (JIEM), 2015)
Purpose: Nowadays it is very difficult for Chinese retired soldiers to find proper jobs, and the primary reason is the significant gap between job requirements and soldiers owned job skills. Therefore, it is very important to improve the soldiers' job skills and enhance their understanding of employment. Design/methodology/approach: This paper expands the study scope from the soldiers' job skills to the employability, initiatively introduces the employment attitude which has obvious impact on the employment of soldiers, and analyses the influence that employment attitude can play on employability. At last, this paper develops statistical method to find the relationship between soldiers' employment attitude and employability. Findings: The empirical analysis shows that soldiers' employment attitude has the positive linkage with employability, which makes the employment attitude a measurable variable for the employability rather than an absolute standard. Research limitations/implications: According to the research purpose, more variables should be considered in the model, consequently, there are only three indicators to describe solders' employment attitude and four indicators to describe solders' employability. Originality/value: This paper takes research on soldiers' employability in a new perspective. The soldiers' employment attitude is served as the entry point, showing the influence that soldiers' employment attitude has on employability.
Keywords: 650; retired soldiers; independent choosing profession; job skills training; employment attitude; employability